Revisiting the Effects of Unemployment Insurance Extensions on Unemployment: A Measurement Error-Corrected Regression Discontinuity Approach - Steven G. Dieterle; Otávio Bartalotti; Quentin Brummet (Institute of Labor Economics (IZA), 2018)
We document two potential biases in recent analyses of UI benefit extensions using boundary-based identification: from using county-level aggregates and from across-border policy spillovers. To examine the first bias, we use a regression discontinuity (RD) approach that accounts for measurement error in county-level aggregates. Our results suggest much smaller effects than previous studies, casting doubt on the applicability of border-based designs. We then document substantial spillover effects of UI benefit duration in the form of across-border work patterns that are consistent with increased tightness in high benefit states, providing evidence against a dominant vacancy reduction response to UI extensions.
Keywords: J61; J65; 330; unemployment insurance; great recession; geographic regression discontinuity; policy spillover